AUDIT QUALITY, OWNERSHIP CONCENTRATION AND EARNINGS MANAGEMENT: EVIDENCE FROM QUOTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
The study examines the effect of audit quality and ownership concentration on earnings management. The study adopts the ex post facto research design. A total of twenty-one (21) firms in the consumer goods sector were selected based on a purposive sampling technique. The study utilised longitudinal data from annual financial reports for the period 2011 to 2017. The data were analysed using multiple regression technique with the aid of E-views, 9.0. The results showed a non-significant negative effect of audit firm size on accruals quality; but, a significant negative effect of ownership concentration on accruals quality. The interaction of ownership concentration and audit firm size had a significant negative effect. Based on this, the study recommends that the issue of earnings management be given due considerations by regulatory authorities through effective ownership structure in corporations. The study further recommends a combination of alternative governance mechanisms in curbing managerial opportunistic behavior. The study discusses limitations inherent in the study.
Keywords: Accruals.; Audit Quality; Earnings Management; Ownership Concentration